KARAKTERISTIK BIOAKUSTIK DAN TINGKAH LAKU LUMBA-LUMBA JANTAN HIDUNG BOTOL (Tursiops aduncus) - Muhammad Zainuddin Lubis; Pratiwi Dwi Wulandari; Totok Hestrianoto (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Bioacoustic is the science that combines biology and acoustics are usually refers to research on sound production, dispersion through elastic media, and reception in animals, including humans .This study observed the behavior male dolphins by doing science approach bioakustik who viewed the characteristics of these dolphins. Male dolphins (Tursiops aduncus) that maintained at Taman Safari Indonesia, Cisarua Bogor has the lowest intensity value amounting to 28.03 dB and the highest amounted to 32.01 dB. Average parameters is measurable salinity of 30 ppm and a temperature of 23 Â°C with the depth of the pool is 4.5 meter. Range frequency clicking sound with the highest intensity value that is equal to 32 dB with a clicking sound 3 after dinner on day 2 contained in the frequency range ie 1400-1600 Hz. Click sound frequency range of male dolphins (Tursiop aduncus) in Taman Safari have frequency 1400- 1500 Hz.